Ice nucleation activity of diesel soot particles at cirrus relevant temperature conditions: Effects of hydration, secondary organics coating, soot morphology, and coagulation. Issue 7 (12th April 2016) - Kulkarni, Gourihar; China, Swarup; Liu, Shang; Nandasiri, Manjula; Sharma, Noopur; Wilson, Jacqueline; Aiken, Allison C.; Chand, Duli; Laskin, Alexander; Mazzoleni, Claudio; Pekour, Mikhail; Shilling, John; et al.
Abstract: Ice formation by diesel soot particles was investigated at temperatures ranging from −40 to −50°C. Size‐selected soot particles were physically and chemically aged in an environmental chamber, and their ice nucleating properties were determined using a continuous flow diffusion type ice nucleation chamber. Bare (freshly formed), hydrated, and compacted soot particles, as well as α ‐pinene secondary organic aerosol (SOA)‐coated soot particles at high relative humidity conditions, showed ice formation activity at subsaturation conditions with respect to water but below the homogeneous freezing threshold conditions. However, SOA‐coated soot particles at dry conditions were observed to freeze at homogeneous freezing threshold conditions. Overall, our results suggest that heterogeneous ice nucleation activity of freshly emitted diesel soot particles are sensitive to some of the aging processes that soot can undergo in the atmosphere. Key Points: Ice nucleating ability of fresh soot particles is similar to hydrated and compact particles Organic‐coated particles required homogeneous freezing threshold conditions Soot particles with aqueous organics nucleated ice via immersion freezing mechanism